Pandemi dalam Tafsir Sufi: Dialektika Trilogi Sufistik ‘Abd al-Qādir al-Jīlānī, Ibn ‘Arabī dan Achmad Asrori al-Ishaqi - Chafid Wahyudi; Ainul Yaqin (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
The pandemic has reignited longstanding tensions between science and religion, transforming their once harmonious relationship into an intense conflict. This discord has cast a shadow on the credibility of religion in the midst of the pandemic and the evolution of scientific civilization. This study presents a religious discourse through the Sufi trilogy of ‘Abd al-Qādir al-Jīlānī, Ibn ‘Arabī, and Achmad Asrori al-Ishaqi. Within this interpretative framework, al-Jīlānī suggests the pandemic symbolizes destiny and human misbehavior consequences. Ibn ‘Arabiī views it as part of the Absolute phenomenon, while al-Ishaqi sees it as a reflection of an unfriendly human-nature relationship. This exploration aims to provide nuanced insights, transcending binary conflicts, and fostering a comprehensive understanding of the challenges posed by the pandemic within the context of science and religion integration.